Vpliv informacijsko-komunikacijskih tehnologij na velikost socialnih omrežij v kontekstu lokalno-globalnih dinamik - Lenarčič, Blaž (Teorija in praksa, 2014)
Paper aims to explore the transition from interpersonal relationship based on territory to the network and thus to some extent, from the local to the global level. Author derives from temporal and territorial independent functioning of information-communication technologies, which are the main means of contemporary human connectivity. In this sense, on the basis of secondary empirical data analysis paper questions the size, structure, and (territorial) range of today's social networks. In addition, the author presents that in a society whose functioning largely bases on information-communication technologies is no longer necessary consistency between the physical and social space, thereby indicates the direction of further deteritorialization of social organization.
Keywords: cyberspace; global; globalno; informacijsko-komunikacijske tehnologije; information-communication technologies; kibernetski prostor; local; location; lokacija; lokalno; social networks; socialna omrežja